2019
DOI: 10.1016/j.jhevol.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Wild chimpanzees deprived a leopard of its kill: Implications for the origin of hominin confrontational scavenging

Abstract: This study reports the first observed case of wild chimpanzees (Pan troglodytes) obtaining animal prey freshly killed by a sympatric leopard (Panthera pardus) and scavenging it with the leopard still nearby. This observation has important implications for the emergence of confrontational scavenging, which may have played a significant role in human evolution. Many scholars agree that eating meat became important during human evolution, and hominins first obtained meat by scavenging. However, it is debatable wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…While Pickering and Wallis () did not provide tooth mark measurements, the overall similarity in shape and size of the tooth marks inflicted by these captive chimpanzees on ungulate postcranial bones to the tooth marks on the chimpanzee cranium studied here means we cannot reject the possibility that chimpanzees inflicted the tooth marks on this cranium. This possibility is also supported by observations of chimpanzee lethal aggression and cannibalism (e.g., Pruetz et al, ; Wilson et al, ) as well as confrontational scavenging (Nakamura et al, ), whether they occurred around or after the time of death.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…While Pickering and Wallis () did not provide tooth mark measurements, the overall similarity in shape and size of the tooth marks inflicted by these captive chimpanzees on ungulate postcranial bones to the tooth marks on the chimpanzee cranium studied here means we cannot reject the possibility that chimpanzees inflicted the tooth marks on this cranium. This possibility is also supported by observations of chimpanzee lethal aggression and cannibalism (e.g., Pruetz et al, ; Wilson et al, ) as well as confrontational scavenging (Nakamura et al, ), whether they occurred around or after the time of death.…”
Section: Discussionmentioning
confidence: 66%
“…Tooth marks have regularly been used to confirm carnivore involvement in bone assemblage formation (Domínguez‐Rodrigo & Piqueras, ; Plummer & Stanford, ; Selvaggio & Wilder, ). In particular, tooth marks on bone have contributed to our understanding of ape diets and dietary behaviors (e.g., scavenging), and of apes as prey (de Ruiter & Berger, ; Domínguez‐Rodrigo & Piqueras, ; Nakamura et al, ; Nakazawa et al, ; Pickering et al, , ). Taphonomic observations, in combination with studies of predator behavior (e.g., Gandini & Baldwin, ; Pierce, ), indicate that predation of large‐bodied apes may be more common than is regularly recognized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimpanzees in all habitats where they are found in the wild eat meat (Moore et al, 2017), as do bonobos (Wakefield et al, 2019), leading many to think that the LCA did as well. Sometimes the meat chimpanzees consumed Is scavenged (Nakamura et al, 2019) but relatively rarely (compared to other foods in their diet). More often the meat is eaten fresh from kills, though chimpanzees exhibit great variability between communities in success, technique, and seasonality of hunting behavior (Moore et al, 2017;Figure 2).…”
Section: The Stomachmentioning
confidence: 99%
“…Another intriguing new paper (Nakamura et al 2019) reports the first observed case of wild chimpanzees (Pan troglodytes schweinfurthii) obtaining animal prey freshly killed by a sympatric leopard (Panthera pardus), scavenging it with the leopard still nearby. This observation has important implications for the emergence of confrontational scavenging.…”
Section: Figmentioning
confidence: 99%